COVID-19 lockdown and seasonal allergic rhinitis: our experience in 40 patients - Gelardi, Matteo; Trecca, Eleonora; Fortunato, Francesca; Iannuzzi, Lucia; Ronca, Gianluca; Quaranta, Nicola; Cassano, Michele (Acta Biomedica Atenei Parmensis, 2021)
Introduction: The aim of this article was to study the course of seasonal allergic rhinitis during COVID-19 lockdown in order to understand if being quarantined at home for a long time can constitute a protective factor for allergic patients.Materials and methods: Telehealth consultations were performed by the departments of Otolaryngology of Foggia and Bari University Hospitals. Participants took part in a phone interview and were asked about their sinonasal symptoms during the COVID-19 lockdown, by answering the sinonasal outcome test (I-SNOT-22) questionnaire. Further data concerning the medications used to treat allergy and the number of days per month in which they were used were collected. The responses about the COVID-19 lockdown were compared to those obtained by the same patients in our clinics the previous year. The statistical analysis was executed by using the paired sample t-test and the Bartlett test considering as significant values with p values